Role and place of immunomodulation therapy in the treatment of infectious inflammatory diseases in combination with secondary immune deficiency - L. V. Luss (Медицинский совет, 2013)
Recent advances in immunology show that virtually all processes in the body and, consequently, all diseases are caused by immune disorders to a certain extent. The immune system recognizes and eliminates foreign compounds - antigenes, both exogenous and endogenous, while innate and acquired immunity regulates homeostasis [11, 12].